2007
DOI: 10.1086/516667
|View full text |Cite
|
Sign up to set email alerts
|

The Short‐Term Effect of Grade Retention on Peer Relations and Academic Performance of At‐Risk First Graders

Abstract: Using latent variable structural equation modeling, we tested a theoretical model positing that grade retention has a positive effect on children's teacher-and peer-rated academic competencies and on sociometric measures of peer acceptance. We also expected that the positive effect of grade retention on peer acceptance would be mediated by children's ability to meet academic challenges in their classrooms. Participants were 350 (52.6% male) ethnically diverse and academically at-risk first graders attending 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…Retention continues to be a common form of intervention for students who have been deemed unprepared for the next level of cognitive and social development, despite the known deleterious impacts on student dropout rate, attitudes towards school, and engagement (Schnurr, Kundert, & Nickerson, 2009). Schnurr et al (2009) cite multiple examples of research on retention and academic outcomes, with findings indicating small short-lived improvements in achievement (Jimerson, 2001;Gleason, Kwok, & Hughes, 2007) but no long-term improvement for retained students (Holmes & Matthews, 1984;Holmes, 1989;Jimerson, 2001). Further, the long-term impacts of retention on student performance have been shown to be nonsignificant (Jimerson, 1999;Silberglitt, Jimerson, Burns, & Appleton, 2006;Jimerson & Ferguson, 2007).…”
Section: Grade Repetition (Retention)mentioning
confidence: 99%
“…Retention continues to be a common form of intervention for students who have been deemed unprepared for the next level of cognitive and social development, despite the known deleterious impacts on student dropout rate, attitudes towards school, and engagement (Schnurr, Kundert, & Nickerson, 2009). Schnurr et al (2009) cite multiple examples of research on retention and academic outcomes, with findings indicating small short-lived improvements in achievement (Jimerson, 2001;Gleason, Kwok, & Hughes, 2007) but no long-term improvement for retained students (Holmes & Matthews, 1984;Holmes, 1989;Jimerson, 2001). Further, the long-term impacts of retention on student performance have been shown to be nonsignificant (Jimerson, 1999;Silberglitt, Jimerson, Burns, & Appleton, 2006;Jimerson & Ferguson, 2007).…”
Section: Grade Repetition (Retention)mentioning
confidence: 99%
“…Gleason et al (2007) found improvements in peer acceptance and teacher/peer perceived academic competence in the repeat year. These studies confirmed the immediate gains in peerrated liking for children retained relative to those who were promoted; however, this research concluded that the benefits dissipated within a few years post-retention.…”
Section: Advantages and Disadvantages Of Grade Repetitionmentioning
confidence: 89%
“…This struggle-succeed-struggle scenario for academic and behavioral outcomes required more research to fully comprehend the long-term consequences for student academic motivation and achievement. Gleason et al (2007) longitudinal, quantitative research affirmed that this scenario may have long-lasting negative consequences, as well as provide an explanation as to why repeated students became disaffected with school. According to Gleason et al (2007) the positive effects of early grade repetition were most often short-term and difficult to compare.…”
Section: Advantages and Disadvantages Of Grade Repetitionmentioning
confidence: 91%
See 2 more Smart Citations